Association of IL-10, IL-18, and IL-33 genetic polymorphisms with recurrent pregnancy loss risk in Iranian women. (3rd April 2019) - Soheilyfar, Sorour; Nikyar, Tahereh; Fathi Maroufi, Nazila; Mohebi Chamkhorami, Fariba; Amini, Zahra; Ahmadi, Mahsa; Haj Azimian, Saba; Isazadeh, Alireza; Taefehshokr, Sina; Taefehshokr, Nima
Abstract: Recurrent pregnancy loss (RPL) is a heterogeneous disease with three or more consecutive abortions before 20 weeks of pregnancy. Recently, inflammatory factors such as interleukins (IL) have been found to be a significant factor in the RPL. The objective of this study was to investigate the association between RPL and IL-10 (rs1800896), IL-18 (rs1946518) and IL-33 (rs1929992) genes polymorphisms in Iranian women. The study participants consisted of 300 women with RPL and the control group comprised of 300 healthy women with successful delivery. Genomic DNA was extracted from peripheral blood, and genotyping was performed by polymerase chain reaction (PCR) followed by restriction fragment length polymorphism (RFLP). There were no significant differences in the frequencies of genotype and allele in IL-10 gene polymorphism (rs1800896) between patients and control group ( p  > .005). In contrast, there were significant differences in the frequencies of CC genotype in IL‐18 gene polymorphism (rs1946518) between patients and the control groups ( p  = .004; OR =0.990; 95% CI: 0.320–8.855). Also, there were significant differences in the frequencies of GA genotype in IL‐33 gene polymorphism (rs1929992) between patients and the control groups ( p  = .001; OR =0.955; 95% CI: 0.239–9.807). Present study showed that the rs1800896 polymorphism (IL-10) might not play role in RPL in the Iranian population; whereas rs1946518 (IL-18) and rs1929992 (IL-33) polymorphisms may be associated with the risk of RPL in the Iranian women.